Engineering mathematics - Bird, John O. (Routledge, 2014)
"John Bird's approach to mathematics, based on numerous worked examples and interactive problems, is ideal for students of a wide range of abilities. Theory is kept to a minimum, with the emphasis firmly placed on problem-solving skills, making this a thoroughly practical introduction to the mathematics that students need to master. The extensive and thorough topic coverage makes this an ideal text for a range of level 2 and 3 vocational courses including the BTEC National specifications. Now in its seventh edition, Engineering Mathematics has helped thousands of students to succeed in their exams. The new edition includes a section at the start of each chapter to explain why the content is important and how it relates to real life. It is also supported by a fully updated companion website with resources for both students and lecturers. It has full solutions to all 1800 further questions contained in the 237 practice exercises. All 525 illustrations used in the text can also be downloaded for use in the classroom" -- Provided by publisher.